2015
DOI: 10.1002/acr.22628
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Reactivation in Patients With Rheumatoid Arthritis: Analysis of Disease Characteristics and Disease‐Modifying Antirheumatic Drugs

Abstract: Objective. To identify the rheumatoid arthritis (RA) characteristics associated with increased herpes zoster (HZ) risk in the Corrona registry RA patients, and to evaluate the risk in initiators of tumor necrosis factor inhibitors (TNFi) or non-TNFi biologic agents or (among those who were currently on or had been previously treated with methotrexate [MTX]) conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) other than MTX. Methods. Cox regression modeling estimated the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 30 publications
(62 reference statements)
2
56
0
5
Order By: Relevance
“…One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1). 15 In total, six studies,21 44–48 performed in European and American datasets, of which four were at low risk of bias, focused on the occurrence of herpes zoster, most of them reporting no increased risk for this type of infection in patients on TNFi (no studies for other bDMARDs), particularly the studies at low risk of bias and/or those that had been adjusted for dropouts 21 44–46…”
Section: Resultsmentioning
confidence: 99%
“…One study comparing bDMARDs with the general population reported standardised incidence rates of 16–20 for tumour necrosis factor-α inhibitor (TNFi) and even higher for RTX (table 1). 15 In total, six studies,21 44–48 performed in European and American datasets, of which four were at low risk of bias, focused on the occurrence of herpes zoster, most of them reporting no increased risk for this type of infection in patients on TNFi (no studies for other bDMARDs), particularly the studies at low risk of bias and/or those that had been adjusted for dropouts 21 44–46…”
Section: Resultsmentioning
confidence: 99%
“…However, despite using validated methods to identify cases of HZ,11 we did not have access to medical records to confirm events, nor do we know of the existence of a validation study for incident HSV. While we were unable to adjust for RA disease activity and severity, we made abatacept our referent exposure group given that it is often used as a second or later line agent in patients that may be more comparable with tofacitinib-treated patients 20. Finally, we recognise the potential for surveillance bias if patients initiating tofacitinib were counselled about zoster risk and thus might be more likely to present for evaluation of suspected HZ to a physician.…”
Section: Discussionmentioning
confidence: 99%
“…In the SABER collaboration, a baseline use of 10 mg/day or more was associated with an increased risk of HZ among rheumatic disease patients compared to no baseline steroid use (aHR 2.13 [95% CI 1.64, 2.75]) [60]. In the CORRONA registry, a prednisone dose of at least 7.5 mg/day was associated with increased risk of HZ among RA patients (HR 1.78 [95% CI 1.20, 2.63]) compared to no glucocorticoid use [61]. …”
Section: Herpes Zoster (Hz)mentioning
confidence: 99%